2014
DOI: 10.1002/jbm.b.33274
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of DLC coated microdimples on hip prosthesis heads

Abstract: Diamond like carbon (DLC) is applied as a thin film onto substrates to obtain desired surface properties such as increased hardness and corrosion resistance, and decreased friction and wear rate. Microdimple is an advanced surface modification technique enhancing the tribological performance. In this study, DLC coated microdimples were fabricated on hip prosthesis heads and their mechanical, material and surface properties were characterized. An Electro discharge machining (EDM) oriented microdrilling was util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The coating thickness was 1.05–1.15 μ m for DLC coating (figure 2(b)). Previous studies on DLC coating also showed a similar coating thickness value [5, 23]. …”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…The coating thickness was 1.05–1.15 μ m for DLC coating (figure 2(b)). Previous studies on DLC coating also showed a similar coating thickness value [5, 23]. …”
Section: Resultssupporting
confidence: 66%
“…Carbon should be the main composition on the coating layer; it also contains chromium, as it was used as an interlayer during the deposition process in order to increase the bonding strength between coating and titanium alloy substrate [5]. Furthermore, some pores, as well as lighter-colored bumps, may exist on the coating surfaces (figure 2(a)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies showed that the sp 2 and sp 3 structure of the nanomultilayer coating determines the high hardness and self-lubricating characteristic, and the selflubrication characteristic of the graphitic coating helps the steady COF. 24,28 The nanomultilayer coatings have a low average COF of 0.1, and it is a lower value compared with other coating such as DLC in literature, 41,42 but the COF may be affected by the testing conditions in different studies. Thus, microstructure and mechanical tests showed that the carbon-based nanomultilayer coatings have desirable mechanical and tribological properties.…”
Section: Discussionmentioning
confidence: 94%